Weight Analysis of Atmospheric Aging of Polycarbonate Impact Factors Based on MIV Method - YANG Bin; LI Jing-yang; WEN Lei (Cailiao gongcheng, 2018)
The mean impact value (MIV) method which is an effective factor weight analysis method was used to quantitatively analyze the effect weight of 15 impact factors on the aging properties of polycarbonate (chromatic aberration, tensile strength, elongation at break, and bending strength) and the corresponding exposure time, climatic factors and environmental factors. The impact factors were exposure time, mean temperature, humidity, sunshine hours, precipitation, wind speed, sea salt ion, SO2, HCl, NO2, H2S, sulfation rate, NH3, water soluble dust fall, and non-water soluble dust fall. The results show that with the regulation rate increasing from 15% to 25% gradually, for the certain aging property, the effect weight of certain impact factor change little, while the sensitivities of aging properties to various impact factors are different; the climatic factors and exposure time are the greatest factors influencing the aging properties of polycarbonate, among environmental factors, the influence of dust fall quantity on the aging properties is the largest; exposure time is the main impact factor influencing chromatic aberration and elongation at break, mean relative humidity has the greatest impact on tensile strength and bending strength.